1978
DOI: 10.3109/03630267809005352
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fetal and Adult Hemoglobins in Culture by Human Umbilical Cord Blood Erythropoietic Precursors

Abstract: We cultured human umbilical cord blood and adult peripheral blood erythropoietic precursors in methylcellulose clonal assay and measured the synthetic rates of HbA, A2, and F. Hb was labeled with 14C-amino acid in culture and separated by slab-gel isoelectric focusing and quantitated by autoradiography. While the mean percentage of HbF synthesized by adult cells was only 20.1%, that of umbilical cord blood cells was 53.9%, which corresponds closely to the biosynthetic capabilities of umbilical cord blood retic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

1979
1979
1983
1983

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Whether or not bone marrow BFU-E in pregnant women are different in their capability to produce HbF in vitro compared to nonpregnant subjects has not been investigated. In other conditions in which the HbF in blood is increased, such as sickle cell anemia, both peripheral blood and bone marrow BFU-E produce significantly increased amounts of HbF in vitro (7,8,27).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Whether or not bone marrow BFU-E in pregnant women are different in their capability to produce HbF in vitro compared to nonpregnant subjects has not been investigated. In other conditions in which the HbF in blood is increased, such as sickle cell anemia, both peripheral blood and bone marrow BFU-E produce significantly increased amounts of HbF in vitro (7,8,27).…”
Section: Methodsmentioning
confidence: 99%
“…The more ma- ture erythroid progenitor cells, colony-forming units that respond to erythropoietin (CFU-E), are present in bone marrow, but not in normal adult peripheral blood (4,5,21). Operationally, CFU-E from adult individuals can be distinguished from BFU-E by the much lower amount of erythropoietin required for growth in vitro, the shorter time necessary for colony formation, the much smaller size and compact appearance of the colonies, and their inability to synthesize HbF in vitro (7,8,22). In the present study, no CFU-E-derived colonies could be identified with confidence in cultures of peripheral blood mononuclear cells from pregnant women.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…F cells contain both Hb A and Hb F, and they are derived from the same pluripotent stem-cell progenitors as the erythrocytes that fail to express Hb F (3)(4)(5). When erythroid progenitors [erythroid burst-forming unit(s); BFUe(s)] from adult persons are used for culture, reactivation of Hb F synthesis appears in the clones (6)(7)(8)(9). Hence, cultures of BFUes provide a tool for investigating the cellular mechanisms controlling the expression of Hb F in adult cells.…”
mentioning
confidence: 99%